Searching the genome of beluga (Huso huso) for sex markers based on targeted bulked segregant analysis (BSA) - Khodaparast, M.; Keyvanshokooh, S.; Pourkazemi, M.; Hosseini, S.J.; Zolgharnein, H. (2014)
In sturgeon aquaculture, where the main purpose is caviar production, a reliable method is needed to separate fish according to gender. Currently, due to the lack of external sexual dimorphism, the fish are sexed by an invasive surgical examination of the gonads. Development of a non-invasive procedure for sexing fish based on genetic markers is of special interest. In the present study we employed Bulked Segregant Analysis (BSA) methodology to search for DNA markers associated with the sex of the beluga sturgeon (Huso huso). DNA bulks (male and female) were created by combining equal amounts of genomic DNA from 10 fish of both sexes. A total of 101 decamer primers associated with the sex-specific sequences in non-sturgeon species was used for targeted screening of the bulks, resulting in 2846 bands that all of them were present in both sexes. Our results showed that sex chromosomes are weakly differentiated in the sturgeon genome and comprised sequences not complementary to the sex-specific primers in non-sturgeon species.